2021
DOI: 10.1371/journal.pone.0254476
|View full text |Cite
|
Sign up to set email alerts
|

Curing or causing? HIV/AIDS in health care system of Punjab, Pakistan

Abstract: Background Pakistan’s National AIDS Control Program has registered 44,000 HIV/AIDS patients to date, but the actual number of cases have been estimated to be as high as 150,000–170,000. The health care system has a very important role to play in this equation and must be reformed to improve the health care services in Pakistan, with regards to HIV/AIDS. Methods It was a qualitative research employing a phenomenological approach. The principal researcher visited nine public and private health care facilities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…Although resources have been stepped up in Pakistan for the last 5 years in response to HIV, little policy attention has been paid to the needs of PLWHA in mental health (61,62). A challenge for this resource-restricted nation is to create structures, skilled staff, and resources to enhance mental health services in general and, in particular, to meet the needs of people living with HIV (63,64). Our findings support the need for more research into HIV-psychological manifestations and identify those who are most vulnerable and develop interventions to reduce the individual and social factors that exacerbate vulnerability to depression and anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Although resources have been stepped up in Pakistan for the last 5 years in response to HIV, little policy attention has been paid to the needs of PLWHA in mental health (61,62). A challenge for this resource-restricted nation is to create structures, skilled staff, and resources to enhance mental health services in general and, in particular, to meet the needs of people living with HIV (63,64). Our findings support the need for more research into HIV-psychological manifestations and identify those who are most vulnerable and develop interventions to reduce the individual and social factors that exacerbate vulnerability to depression and anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Pakistan is among the developing Asian countries where inadequate infrastructural arrangements and mishandling of hospital waste are reported frequently (Abdullah et al 2021 ; Ahmed Bin Hassan and Mubashar Hassan Zia 2020 ; Arub et al 3 ; Ayub et al 2019 ; Khan et al 2020 ; Naz et al 2020 ). In opposition to the guidelines and rules laid down by WHO and the Ministry of Climate Change (MoCC) of Pakistan, unsafe and illegal disposal of hospital waste is reported in electronic and press media.…”
Section: Current Practice In Pakistanmentioning
confidence: 99%
“…By 18 May 2019, health officials had discovered 571 (3.4 percent) new instances of HIV infection among 16,856 people tested, 463 (81 percent) of which were in children and adolescents aged 15 years, including 355 (62 percent) in children under 5 years [ 4 ]. Because of insufficient information flow and scarce diagnostic facilities, estimates of PLHIV are substantially higher than the actual number of recorded cases [ 5 ]. The preliminary investigations (including patient interviews, site visits to clinics, hospitals and blood banks and a review of surveillance data) identified unsafe injection practices at health care facilities, unsafe practices at blood banks, inadequate infection control measures and improper medical waste management as the possible risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…The SACP advised that infection prevention and control, as well as blood safety, need to be improved by training health care personnel in terms of safe injection techniques, forming task groups with key stakeholders and implementing policy reforms and laws [ 4 ]. In a society with a low literacy rate, where many health views are driven by myths and fallacies and with a poorly underutilized public health system, illnesses such as HIV take on a much larger magnitude due to financial, social and political obstacles [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation